Efektifitas Penggunaan Explosion Box Dalam Meningkatkan Sosial Emosional Anak Usia Dini di Raudlatul Athfal Muslimat NU 81 Nurul Falah Banjarsari - Khasanah, Nur Fikriyatul; Maarif, Nina Nuriyah; Fithriyah, Kais Nabila (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2025)
Early childhood education primarily aims to support the physical and psychological development of children outside the home environment before they enter elementary school. At this stage, key areas of development include motor skills, cognitive abilities, language, and social-emotional growth. This study explores the use of